Household Energy Poverty: Evidence From a Large-Scale Longitudinal Survey - Septiani, Yustirania; Sugiharti, Rr Retno; Panjawa, Jihad Lukis; Nur Izati, Isna Hana (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
Energy is a basic household necessity closely related to human health and well-being; unfortunately, not all households have equal access to energy. This condition is referred to as energy poverty, wherein a household lacks access to or cannot afford basic energy services to meet its daily needs. The goal of this research is to analyze the determining factors of the probability of households experiencing energy poverty in Indonesia, focusing on Household Demography and Household Expenditure factors. Using household survey data from IFLS4 (2007) and IFLS5 (2014) and employing Multinomial Logit analysis, this study aims to capture the differences between groups of energy-consuming households. The research findings indicate that households found it easier to access energy (especially gas) after the implementation of the energy conversion policy from kerosene to gas, which began in 2007. Based on the estimation results, the probability of households experiencing energy poverty in Indonesia in 2007 is determined by Education, Income, Spouse Work, Communication Cost, and Health Cost, while in 2014, it is influenced by Education, Spouse Work, Electric Cost, Fuel Cost, Health Cost, and Non-food Consumption. Other indicators of Household Demography and Household Expenditure show different results for each category and period. To address energy poverty, a change in perspective and reform of programs in the energy sector are required. The government can also provide energy subsidies and compensation to poor and vulnerable populations.